2012
DOI: 10.1186/1556-276x-7-396
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured porous silicon micropatterns as a tool for substrate-conditioned cell research

Abstract: The localized irradiation of Si allows a precise patterning at the microscale of nanostructured materials such as porous silicon (PS). PS patterns with precisely defined geometries can be fabricated using ion stopping masks. The nanoscale textured micropatterns were used to explore their influence as microenvironments for human mesenchymal stem cells (hMSCs). In fact, the change of photoluminescence emission from PS upon aging in physiological solution suggests the intense formation of silanol surface groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…This application area involves different types of sensors, including electric, electrochemical, optical, and labeling devices [15][16][17]. Biosensor application of por-Si also includes the use in passive platforms for the deposition of biological cultures and active elements interaction with the biological environment [15,18,19]. A highly developed porous structure of por-Si facilitates the development of highly efficient parallel biochips for the analysis of several cultures in one platform.…”
Section: Introductionmentioning
confidence: 99%
“…This application area involves different types of sensors, including electric, electrochemical, optical, and labeling devices [15][16][17]. Biosensor application of por-Si also includes the use in passive platforms for the deposition of biological cultures and active elements interaction with the biological environment [15,18,19]. A highly developed porous structure of por-Si facilitates the development of highly efficient parallel biochips for the analysis of several cultures in one platform.…”
Section: Introductionmentioning
confidence: 99%
“…However, Galeazzo et al (2001) stated that RTA was adequate to recover the crystalline structure. Punzon-Quijorna et al (2012) have shown that implantation of MeV Si ions is also an effective tool for the localized formation of PSi in the micrometer range. It is known that irradiation of materials with MeV heavy ions produces defects in semiconductors along the ion tracks, and the damaged part of the material, depending on the type of material itself, may turn more sensitive or more resistant to chemical etching.…”
Section: Mask Technologymentioning
confidence: 99%
“…It is known that irradiation of materials with MeV heavy ions produces defects in semiconductors along the ion tracks, and the damaged part of the material, depending on the type of material itself, may turn more sensitive or more resistant to chemical etching. Punzon-Quijorna et al (2012) have found that in the case of heavier ions, its higher damage efficiency allows lower implantation doses to achieve PSi growth inhibition, which allows shorter process times, and at the same time provides good lateral resolution below the micrometric range. As it is seen in Figure 3.7, porous silicon growth is inhibited on irradiated substrates already with Si fluences greater than 10 12 ion/cm 2 in the energy range of 5-24 MeV.…”
Section: Mask Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this particular case, the selective formation of nanoPS allows the development of a wide variety of photonic devices including waveguides and photonic crystals [16,17]. In addition, due to the biocompatibility of Si and nanoPS, these patterns have been also used for the fabrication of tailored platforms for cell adhesion [18,19]. However, none of these methods have the capability to offer flexibility in the pattern design in a timeefficient process, over large areas, and in a single-step process.…”
Section: Introductionmentioning
confidence: 99%